The Gut Microbiota in Liver Transplantation Recipients During the Perioperative Period - Lai, Zhiyong; Chen, Zongkun; Zhang, Anhong; Niu, Zhiqiang; Cheng, Meng; Huo, Chenda; Xu, Jun (Frontiers in Physiology, 2022)
Background Chronic liver disease is a global problem, and an increasing number of patients receive a liver transplant yearly. The characteristics of intestinal microbial communities may be affected by changes in the pathophysiology of patients during the perioperative. Methods We studied gut fecal microbial community signatures in 37 Chinese adults using 16S rRNA sequencing targeting V3-V4 hypervariable regions, with a total of 69 fecal samples. We analyzed the Alpha and Beta diversities of various groups. Then we compared the abundance of bacteria in groups at the phylum, family, and genus levels. Results The healthy gut microbiota predominantly consisted of the phyla Firmicutes and Bacteroidestes, followed by Proteobacteria and Actinobacteria. Compared with healthy people, due to the dominant bacteria in patients with chronic liver disease losing their advantages in the gut, the antagonistic effect on the inferior bacteria was reduced. The inferior bacteria multiplied in large numbers during this process. Some of these significant changes were observed in bacterial species belonging to Enterococcus, Klebsiella, and Enterobacter, which increased in patients’ intestines. There were low abundances of signature genes such as Bacteroides, Prevotella, and Ruminococcus. Blautia and Bifidobacterium (considered probiotics) almost disappeared after liver transplantation. Conclusion. There is an altered microbial composition in liver transplantation patients and a distinct signature of microbiota associated with the perioperative period.